UNVEILING THE DRIVERS OF TAX AGGRESSIVENESS: THE ROLES OF FINANCIAL DISTRESS, CORPORATE SOCIAL RESPONSIBILITY, AND FIRM SIZE - Ananta Salsabilla Islamia; Sofie Yunida Putri (ZILLZELL MEDIA PRIMA, 2026)
This study focuses on examining tax aggressiveness reflected in the Cash Effective Tax Rate (CETR), which is impacted by financial distress, Corporate Social Responsibility (CSR), and firm size. The study uses information from yearly reports. and financial statements of consumer non-cyclical companies listed on the Indonesia Stock Exchange from 2020 to 2024. The selection of the sample was done using a criterion-based sampling method, resulting in 44 companies with a total of 220 observational data. The analysis process applies panel data regression supported by EViews 13 software. The empirical findings demonstrate that financial distress has an influence on tax aggressiveness. Furthermore, CSR affects tax aggressiveness. Likewise, CSR is linked to tax aggressiveness. Firm size also shows an impact on tax aggressiveness. Collectively, the outcomes suggest that a company’s financial condition, social responsibility practices, and organizational scale contribute to determining its tax management behaviour.